2010
DOI: 10.1128/jvi.01698-09
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Paramecium bursaria Chlorella Virus 1 Transcription

Abstract: Paramecium bursaria chlorella virus 1 (PBCV-1), the prototype of the genus Chlorovirus (family Phycodnaviridae), is a large, icosahedral (190 nm in diameter), plaque-forming virus that infects the unicellular, eukaryotic green alga Chlorella sp. strain NC64A. The PBCV-1 virion has a lipid membrane located inside an outer glycoprotein capsid. The 330-kb genome is a linear, nonpermutated, double-stranded DNA (dsDNA) molecule with covalently closed hairpin ends that has approximately 365 protein encoding genes (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…This percentage is comparable with the observed expression of 65% of viral genes during infection of the marine phytoplankter Emiliania huxleyi by EhV-86 (35). However, recent gene expression studies in PBCV-1 and Mimivirus validated transcription for nearly all of their predicted genes (3,36). It seems therefore likely that our microarray data underestimated the true extent of transcriptional activity in CroV.…”
Section: Resultssupporting
confidence: 82%
“…This percentage is comparable with the observed expression of 65% of viral genes during infection of the marine phytoplankter Emiliania huxleyi by EhV-86 (35). However, recent gene expression studies in PBCV-1 and Mimivirus validated transcription for nearly all of their predicted genes (3,36). It seems therefore likely that our microarray data underestimated the true extent of transcriptional activity in CroV.…”
Section: Resultssupporting
confidence: 82%
“…Thus, a percentage of ORFans might be true functional genes with the same expression potential as non-ORFans, undergoing an equal evolution rate. This conclusion is consistent with different reports showing that 95, 96, 97 and 99% of predicted coding sequences are respectively expressed in Vaccinia, Red Sea bream iridovirus, SGIV, and Paramecium bursaria Chlorella virus-1 at some time during the virus infectious cycle [43][44][45][46][47] . Thus, ORFans represent a high proportion of potentially coding sequences in the current databases, but very few viral ORFans have been experimentally characterized [48] .…”
Section: Are Orfans Functional Genes?supporting
confidence: 93%
“…(43), the cvSOD-encoding gene a245r was expressed as a late gene. A microarray experiment also indicated that the a245r gene was expressed as a late gene (44). The hybridized RNA band was ϳ1.3 kb in size (see Fig.…”
Section: Resultsmentioning
confidence: 90%